Implementation of Sustainable Development Goals (SDGs) in realizing quality education at Daarut Tauhiid Boarding School Putri Junior High School - Meldya, Nisa Kurniasih; Afifah, Fia; Marwah, Siti Aidah; Yunita, Yunita; Suhendi, Endi (Educenter : Jurnal Ilmiah Pendidikan, 2024)
This research is motivated by the fact that there are still several schools that have not been fully able to show efforts in realizing the SDGs goal 4, namely quality education. This study aims to describe and analyze the steps taken in the planning, implementation, and evaluation stages of the implementation of SDGs in realizing quality education at Daarut Tauhiid Boarding School. In addition, this study also identifies the supporting and inhibiting factors in the implementation of SDGs to achieve quality education at the school. This study uses a qualitative approach and case study method with observational data collection techniques, interviews and documentation. Based on the research results, it can be concluded that Daarut Tauhiid Boarding School Putri has implemented the Sustainable Development Goals (SGDs) in realizing quality education with the implementation of the Independent Curriculum and the Daarut Tauhid Islamic Boarding School Curriculum which focuses on character education in the form of good and strong character (BAKU). The BAKU character consists of six character assessments, namely sincerity, honesty, tawadhu, courage, discipline, and resilience. The pesantren curriculum has 4 curriculum pillars, namely: ma'rifatullah, entrepreneurship, leadership, and environmental insight.